Analisis Kinerja Keuangan PT Semen Indonesia (Persero) Tbk. Periode 2018-2022 - Hasanah, Siti (CV. Lafadz Jaya, 2024)
The aim of this research is to determine the financial condition and financial performance at PT Semen Indonesia (Persero) Tbk. The 2018-2022 period is reviewed from the liquidity ratio, solvency ratio, activity ratio and profitability ratio. The method used is quantitative descriptive. The results of calculations using financial ratio analysis show that based on the liquidity ratio seen from the current ratio, quick ratio and cash ratio analysis, it is declared not good because it is below industry standards. Based on the solvency ratio seen from the debt to asset ratio analysis, it is declared not good because it is above industry standards. Judging from the analysis, the debt to equity ratio is declared good because it is above industry standards and the long term debt to equity ratio is declared bad because it is below industry standards. Then, based on the activity ratio seen from the analysis of inventory turnover, fixed asset turnover and total asset turnover, it was declared not good because the company was deemed unable to meet industry standards. Based on the profitability ratio seen from the analysis of net profit margin, return on investment, and return on equity, it is stated that it is not good because it is still below industry standards.